Cardiac Shock Wave Therapy in Coronary Artery Disease: A Systematic Review and Meta-Analysis - Qiu, Quan; Chen, Shenjie; Qiu, Yuangang; Mao, Wei (Frontiers in Cardiovascular Medicine, 2022)
Objective Coronary artery disease (CAD) has been one of the leading causes of morbidity and mortality worldwide. Cardiac shock wave therapy (CSWT) is a novel and non-invasive therapy for CAD. Therefore, we conducted a systematic review and meta-analysis to evaluate the efficacy of CSWT on CAD. Methods and results We performed a comprehensive search of electronic databases such as PubMed, Embase, the Cochrane Library, and Wanfang Data in October 2021. The results were reported as weighted mean difference (WMD) with a 95% confidence interval (CI). Statistical heterogeneity scores were assessed with the standard Cochran’s Q test and the I2 statistic. A total of 8 randomized trials and 2 prospective cohort studies, together involving 643 patients (n = 336 CSWT and n = 307 control), were included in our study. Eight studies with 371 patients showed significantly improved rest left ventricular ejection fraction (LVEF) with CSWT as compared to that of the control group (WMD 3.88, 95% CI 1.53–6.23, p = 0.001, I2 = 51.2%). Seven studies with 312 patients reported left ventricular internal diameter in diastole (LVIDd) were markedly decreased in the CSWT group compared to the control group (WMD −1.81, 95% CI −3.23 to −0.39, p = 0.012, I2 = 20.3%). The summed stress score significantly favored the CSWT group (WMD −3.76, 95% CI −6.15 to −1.37, p = 0.002, I2 = 56.8%), but there was no significant difference for the summed rest score. Our data were acquired from studies without a perceived high risk of bias, so plausible bias is unlikely to seriously affect the main findings of the current study. Conclusion Based on data from our present meta-analysis, CSWT was shown to moderately improve myocardial perfusion and cardiac function among patients with CAD, which would provide the clinicians with a meaningful and valuable option. Systematic Review Registration The meta-analysis was registered on the Open Science Framework (OSF) (https://osf.io/r2xf9).